Embedded system for a bioreactor: application to sugar fermentation - Danilo Paredes; Gonzalo Alvarez; Mauren Fuentes Mora; Ramiro Sanchez (Revista Elektrón)
The focus of this project is on the development and implementation of an embedded system to improve the control and efficiency of a bioreactor. The advantages of this system are examined, highlighting its ability to monitor in real time, ensure accuracy and stability, provide flexibility, enable remote monitoring and telemetry, as well as its potential scalability and cost-effectiveness. The study focuses on the integration of this system in a bioreactor for the fermentation of sugars using microorganisms in order to optimize the accuracy, productivity and quality of the process. A detailed analysis of the technical aspects is provided, including the use of Arduino boards, the programming of these boards and their connection with sensors and actuators for the monitoring and adjustment of critical variables such as temperature and pH. It also highlights the remote connection capability of the system, which allows users to monitor and manage the processes from any location with Internet access. This approach is intended to improve the efficiency and reproducibility of biotechnological processes, as well as to provide greater flexibility and control in their operation.